Potent inhibition of angiogenesis by D,L-peptides derived from vascular endothelial growth factor receptor 2 - Piossek, Christine; Thierauch, Karl-Heinz; Schneider-Mergener, Jens; Volkmer-Engert, Rudolf; Bachmann, Martin F.; Korff, Thomas; Augustin, Hellmut G.; Germeroth, Lothar (Thrombosis and Haemostasis, 2003)
Vascular endothelial growth factor (VEGF) is a potent mitogen for endothelial cells and plays a central role in angiogenesis and vasculogenesis. Therefore, VEGF and its receptors VEGFR-1 and VEGFR-2 are prime targets for anti-angiogenic intervention which is thought to be one of the most promising approaches in cancer therapy. Recently, we have discovered a VEGFR-2-derived peptide (247RTELNVGIDFNWEYP261) representing a potential binding site to VEGF. Using the spot synthesis technique, systematic D-amino acid substitutional analyses of this peptide were conducted and the resulting D, L-peptides inhibit VEGF binding to VEGFR-2 at half maximal concentration of 30 nM.The serum-stable D, L-peptides further inhibited auto-phosphorylation of the VEGFR-2 at nanomolar concentrations. Testing of the peptides in a spheroid-based angiogenesis assay demonstrated a potent anti-angiogenic effect in vitro. The rational design of potent and stable anti-angiogenic peptide inhibitors from their parent receptors provides a feasible route to develop novel leads for anti-angiogenic medicines.
Keywords: VEGFR-2; angiogenesis; endothelial cells; spheroid sprouting assay; D; L-peptides